Effects of oestradiol and tamoxifen on VEGF, soluble VEGFR-1, and VEGFR-2 in breast cancer and endothelial cells - Garvin, S (Nature Publishing Group, 2005)
Angiogenesis is regulated by the balance between pro- and antiangiogenic factors. Vascular endothelial growth factor (VEGF), acting via the receptors VEGFR-1 and VEGFR-2, is a key mediator of tumour angiogenesis. The soluble form of the VEGF receptor-1 (sVEGFR-1) is an important negative regulator of VEGF-mediated angiogenesis. The majority of breast cancers are oestrogen dependent, but it is not fully understood how oestrogen and the antioestrogen, tamoxifen, affect the balance of angiogenic factors. Angiogenesis is a result of the interplay between cancer and endothelial cells, and sex steroids may exert effects on both cell types. In this study we show that oestradiol decreased secreted sVEGFR-1, increased secreted VEGF, and decreased the ratio of sVEGFR-1/VEGF in MCF-7 human breast cancer cells. The addition of tamoxifen opposed these effects. Moreover, human umbilical vein endothelial cells (HUVEC) incubated with supernatants from oestradiol-treated MCF-7 cells exhibited higher VEGFR-2 levels than controls. In vivo, MCF-7 tumours from oestradiol+tamoxifen-treated nude mice exhibited decreased tumour vasculature. Our results suggest that tamoxifen and oestradiol exert dual effects on the angiogenic environment in breast cancer by regulating cancer cell-secreted angiogenic ligands such as VEGF and sVEGFR-1 and by affecting VEGFR-2 expression of endothelial cells.